Risk characterisation of ciguatera poisoning in Europe. Issue 5 (19th May 2021) - Canals, Ana; Martínez, Carmen Varela; Diogène, Jorge; Gago‐Martínez, Ana; Cebadera‐Miranda, Laura; de Vasconcelos, Filipa Melo; Gómez, Inmaculada León; Sánchez, Elena Vanessa Martínez; Alférez, Rocío Carmona; Núñez, Domingo; Friedemann, Miriam; Oleastro, Mónica; et al.
Abstract : The EuroCigua project main objective is to characterize the risk of Ciguatera Poisoning (CP) in Europe including several specific objectives: to determine the incidence of ciguatera in Europe and the epidemiological characteristics of cases; to assess the presence of ciguatoxin in food and the environment in Europe and to develop and validate methods for the detection, quantification and confirmation of the presence of ciguatoxin contaminated specimens. This report compiles the activities carried out during the EuroCigua project from the signing in April 2016 until December 2020. The present document corresponds to Deliverable No. 6: "Final Scientific Report" on Risk characterization of ciguatera food poisoning in Europe of the Specific Agreement no. 1 "MANAGEMENT AND SCIENTIFIC COORDINATION" within the Framework Partnership Agreement GP/EFSA/AFSCO/2015/03 "Risk characterization of ciguatera food poisoning in Europe".